2015
DOI: 10.1099/mic.0.000012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of intracellular trehalose affects formation of Escherichia coli persister cells

Abstract: Persisters are dormant antibiotic-tolerant cells that usually compose a small fraction of bacterial populations. In this work, we focused on the role of trehalose in persister formation. We found that the DotsA mutant, which is unable to synthesize trehalose, produced increased levels of persisters in the early stationary phase and under heat stress conditions. The lack of trehalose in the DotsA mutant resulted in oxidative stress, manifested by increased membrane lipid peroxidation after heat shock. Stationar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…These monosaccharides are central metabolites that can be degraded to obtain energy and biosynthetic building blocks or stored as glycogen (Wilson et al , ; Ruhal et al , ). This is consistent with the earlier studies demonstrating that the Δ otsA mutant exhibited an approximately twofold higher level of UDP‐glucose than the WT strain (Böhringer et al , ) and with our previous study showing that early stationary phase Δ otsA cells accumulated more glycogen than WT cells (Kuczyńska‐Wiśnik et al , ). In the absence of trehalose synthesis in Δ otsA cells, the excess glucose‐6‐phosphate could be converted to pyruvate and then to acetyl‐CoA and AcP (Enjalbert et al , ) that is engaged in nonenzymatic lysine acetylation, which is the dominant form of acetylation in E. coli cultures in stationary phase (Kuhn et al , ; Wolfe, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These monosaccharides are central metabolites that can be degraded to obtain energy and biosynthetic building blocks or stored as glycogen (Wilson et al , ; Ruhal et al , ). This is consistent with the earlier studies demonstrating that the Δ otsA mutant exhibited an approximately twofold higher level of UDP‐glucose than the WT strain (Böhringer et al , ) and with our previous study showing that early stationary phase Δ otsA cells accumulated more glycogen than WT cells (Kuczyńska‐Wiśnik et al , ). In the absence of trehalose synthesis in Δ otsA cells, the excess glucose‐6‐phosphate could be converted to pyruvate and then to acetyl‐CoA and AcP (Enjalbert et al , ) that is engaged in nonenzymatic lysine acetylation, which is the dominant form of acetylation in E. coli cultures in stationary phase (Kuhn et al , ; Wolfe, ).…”
Section: Resultssupporting
confidence: 93%
“…Although it has been well documented that protein aggregation is influenced by trehalose, our previous studies revealed that the formation of protein aggregates was not affected in Δ otsA cells that are unable to synthesize trehalose. The levels and densities of E. coli protein aggregates isolated by two‐step sucrose gradient ultracentrifugation were comparable in WT and Δ otsA cells (Kuczyńska‐Wiśnik et al , ). It is known that sucrose, similar to trehalose, can stabilize proteins (Ferreira et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, persisters have been found to be important to the pathogenesis of infections, including persistent tuberculosis, reoccurring uropathogenic E. coli infections, and Pseudomonas aeruginosa infections in cystic fibrosis patients (10)(11)(12)(13)(14). The rate of persister formation is much higher in stationary-phase cells than in actively growing cells (10,(15)(16)(17)(18)(19). In addition to increasing rates of persister formation, stationary phase can also increase rates of resistance and tolerance to antibiotics (18,(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Recent work on the mechanisms of persister formation suggests that the effects of TA systems are controlled by guanosine pentaphosphate [(p)ppGpp] (11,15), placing persister formation under the control of the stringent response as a result of nutrient exhaustion (reviewed in reference 16). However, protein aggregation (17), trehalose deficiency (18), acid stress (19), biofilm formation (9), the SOS response (20), and quorum sensing (21) are among the additional factors implicated in persister formation. It therefore seems likely that persisters can arise by multiple interconnected pathways and may have selective value in response to stresses or other environmental conditions.…”
mentioning
confidence: 99%